(untitled) (Swiss Medical Weekly, 2015)
PRINCIPLES: Therapeutic target serum concentrations of first-line antituberculosis drugs have not been well defined in clinical studies in tuberculosis (TB) patients. METHODS: We retrospectively investigated the estimated maximum serum concentrations (eCmax) of antituberculosis drugs and clinical outcome of TB patients with therapeutic drug monitoring performed between 2010–2012 at our institution, and follow-up until March 2014. The eCmax was defined as the highest serum concentration during a sampling period (2, 4 and 6 hours after drug ingestion). We compared the results with published eCmaxvalues, and categorised them as either “within reference range”, “low eCmax”, or “very low eCmax”.Low/very low eCmax-levels were defined as follows: isoniazid 2–3/<2 mg/l, rifampicin 4–8/<4 mg/l, rifabutin 0.2–0.3/<0.2 mg/l, ethambutol 1–2/<0.1 mg/l and pyrazinamide <20 mg/l. RESULTS: Concentrations of antituberculosis drugs in 175 serum samples of 17 patients with TB were analysed. In 12 (71%) patients, multiple therapeutic drug monitoring samples were collected over time, in 5 (29%) patients only one sample was available for therapeutic drug monitoring. Overall, 94% of all patients had at least one low antituberculosis drug concentration. Overall, 64% of all eCmax levels were classified as “low” or “very low”. The eCmax was below the relelvant reference range in 80% of isoniazid, 95% of rifampicin, 30% of pyrazinamide, and 30% of ethambutol measurements. All but one patient were cured of tuberculosis. CONCLUSIONS: Although many antituberculosis drug serum concentrations were below the widely used reference ranges, 16 of 17 patients were cured of tuberculosis. These results challenge the use of the published reference ranges for therapeutic drug monitoring.